Platypnoea-Orthodeoxia Syndrome Post Laparoscopic Surgery in a Patient with a Patent Foramen Ovale. Issue 3 (May 2014) - Low, Z.; Darvall, J. N.; Radford, S. T.
Platypnoea-orthodeoxia syndrome has the pathognomonic clinical findings of dyspnoea and arterial hypoxaemia relieved by recumbency. We report on a patient who presented with platypnoea-orthodeoxia syndrome post laparoscopic surgery. Platypnoea-orthodeoxia syndrome is an important diagnosis to consider when investigating hypoxia without an obvious cause.